Mandibular condylar morphology for bruxers with different grinding patterns. Issue 4 (3rd July 2016) - Tao, Jianxiang; Wu, Junhua; Zhang, Xuying
Abstract: Objectives: The purpose of this study was to investigate the mandibular condylar morphology for bruxers with different grinding patterns. Method: Condylar sectional morphology and condylar position of 30 subjects were determined by two viewers using cone beam computed tomography (CBCT) image data sets. The grinding patterns during sleep bruxism (SB) were determined objectively using a Brux-checker device.Chi-square tests were used for statistical analysis for the condylar morphology type between different tooth grinding patterns. Spearman's rank correlation coefficient was used for correlation analysis between condylar position and the canine guidance area during SB. Results: Theincidence of condylarmorphologicaldivergence from idealwas35%.There isa significant difference in distribution of condylar morphology type between the group grinding (GG) and GG combined with mediotrusive side grinding (MG) (p < 0.05). There was no significant correlation between condylar position and canine guidance area during bruxism. Discussion: MG during SB is associated with condylar morphology that is considered not to be ideal.